Propriedades estelares de galáxias compactas massivas no Universo Local - Slodkowski Clerici, K.; Schnorr-Müller, A.; Trevisan, M.; Ricci, T. V. (Cadernos de Astronomia, 2024)
Massive compact galaxies (MCGs) are quiescent galaxies characterized, in this work, with high values of effective velocitydispersion, stellar mass and small values of effective radius. With the aim of investigating the formation and evolutionof MCGs, we determined the properties of the stellar populations of 1858 MCGs derived from the Sloan Digital SkySurvey. We compare the results with a sample of control galaxies (CSGs) (quiescent galaxies with medium sizes) matchedin redshift to the MCGs. We compared the results to the fixed velocity dispersion and found differences between theproperties of the stellar populations, especially for stellar metallicity: MCGs present lower metallicity than CSGs at thefixed velocity dispersion. The results presented are not yet sufficient to determine the evolutionary path of MCGs, butmay indicate differences associated with the initial mass function or the fraction of dark matter within 1 effective radiusin MCGs.
Keywords: Astrophysics; galaxy; dark matter